Congenital Stenosis of the Descending Colon in Children (Clinical Case) - Khujaqulovich, Khayitov Ulugbek (American Journal of Bioscience and Clinical Integrity, 2025)
Congenital stenosis of the colon and descending colon is a rare form of congenital gastrointestinal defect. The diagnosis and differential diagnosis of this disease are characterized by complexity in pediatric surgery practice.Objective. Improving the diagnosis and treatment of congenital intestinal stenosis in children.Material and Methods. The study population consisted of patients treated for colonic intestinal stenosis between 2018 and 2023.Results. After diagnosing descending colon stenosis, colostomy formation surgery was performed on the patient, considering their general condition. Subsequently, a laparotomy was performed to resect the chrysanthemum stenosis and form a kissing anastomosis. A catamnesis study noted that the condition of the anastomosis and the patient’s overall state were satisfactory.Conclusion. Timely diagnosis and treatment of congenital stenosis of the colon require careful attention. In such cases, typical symptoms of this condition include meteorism, vomiting, defecation problems, and slow growth and development in the neonatal period. Pediatric surgeons should carefully investigate the aforementioned symptoms to rule out congenital colon stenosis in children.